CLUSTER ANALYSIS OF SOCIO-ECONOMIC DEVELOPMENT OF RURAL AREAS AND PEASANT FARMS IN THE SYSTEM OF FORMATION OF RURAL TERRITORIAL COMMUNITIES: A CASE STUDY OF VOLYN REGION, UKRAINE - Ivan BALANIUK; Volodymyr KYRYLENKO; Yuliia CHALIUK; Yuliia SHEIKO; Svitlana BEGUN; Liubov DIACHENKO (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
In the article we proved that the clustering of regions in terms of socio-economic conditions of rural development and farms located on them using a selected range of indicators by scientists was not carried out. The obtained results provide an opportunity to conduct a comprehensive assessment and generalization of the territorial differentiation of socio-economic conditions for the development of rural areas and farms located in the Volyn region of Ukraine. Visualization of the territorial-spatial distribution of selected clusters using a cartogram allows optimizing the visual perception of the information load on the clustering results. The general generalizations of regional differentiation of separate elements of social and economic conditions of development of rural territories and peasant farms located on them for real realities prompt to think about perspective prospects of development of the system of these farms, their place, and role in the organizational structure of agrarian sector of market type.